Zimbabwe : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report ;, 2010)
The macroeconomic outlook for 2010 on unchanged policies is daunting. Short-term risks are skewed to the downside and the medium-term outlook is bleak in the absence of significant improvement in policies. The macroeconomic outlook could significantly improve if policies are strengthened. Counting on a significant increase in donor financing and budget revenue, the approved 2010 budget ramped up both wages and capital expenditures. The recent increase in the wage bill has significant adverse macroeconomic implications. The medium-term fiscal position is clearly unsustainable.